Ecodesign for cities and suburbs - Barnett, Jonathan; Beasley, Larry 1948-; SpringerLink (Online service). (Washington, DC Island Press/Center for Resource Economics, 2015)
In six comprehensively illustrated chapters, the authors explain ecodesign concepts, including the importance of preserving and restoring natural systems while also adapting to climate change; minimizing congestion on highways and at airports by making development more compact, and by making it easier to walk, cycle and take trains and mass transit; crafting and managing regulations to ensure better placemaking and fulfill consumer preferences, while incentivizing preferred practices; creating an inviting and environmentally responsible public realm from parks to streets to forgotten spaces; and finally how to implement these ecodesign concepts.
1. Ecodesign: Changing the Urban Growth Model -- 2. Adapting to Climate Change and Limiting -- 3. Balancing Cars and Other Transportation -- 4. Making Cities More Livable and Environmentally Compatible -- 5. Designing and Managing the Public Realm -- 6. Implementing Ecodesign -- Art Credits -- Notes -- Index.
Electronic reproduction.
Keywords: Regional planning; Cities and towns -- Growth; City planning -- Environmental aspects; Electronic books